APPLICATION OF CONTEXTUAL TEACHING LEARNING TO LEARNING RESULTS IN UNDERSTANDING THE LIFE ENVIRONMENT IN SMP NEGERI 2 SUKODONO: Elan Artono Nurdin, Fahrudi Ahwan Ikhsan, Fahmi Arif Kurnianto, Bejo Apriyanto - Elan Artono Nurdin; Fahrudi Ahwan Ikhsan; Fahmi Arif Kurnianto; Bejo Apriyanto (Geosfera Indonesia, 2017)
This study aims to determine the improvement of learning outcomes geography by applying Contextual Teaching and Learning (CTL) on the concept of environmental pollution. This research was conducted at SMPN 2 Sukodono, Lumajang. The method used in this study is the method Classroom Action Research (CAR), PTK is implemented as an effort to overcome problems that arise in certain classes. This method is done with four stages, namely planning, action, observation, and reflection. The four stages are cycles that take place repeatedly and carried out with the same steps and focused on learning Contextual Teaching and Learning (CTL). Based on the results research that has been done shows that student learning outcomes increased. This increase can be seen through the cycle have been done. In the first cycle the average student learning outcomes were 54.76 at the time of the pretest and 77.46 at the time of post-test. While in the second cycle the average student learning outcomes 48.33 at pretest and 78.28 at posttest. key words : Contextual Teaching and Learning, Learning Outcomes, SMPN 2 Sukodono References Hamalik, Oemar. 2004. Proses Belajar Mengajar. Bumi Aksara. Jakarta. Mulyasa. 2009. Praktik Penelitian Tindakan Kelas. Bandung: Rosdakarya Nasution. 2004. Sosiologi Pendidikan. Jakarta: PT Rineka Cipta. Sanjaya, Wina. 2009. Strategi Pembelajaran Berorientasi Standar Proses. Pendidikan. Prenada : Jakarta. Sardiman. 2010. Interaksi dan Motivasi Belajar Mengajar. Jakarta: PT. Raja Grafindo. Sukardi. 2009. Metodologi Penelitian Pendidikan(Kompetensi dan Praktiknya). Jakarta: Bumi Aksara Copyright (c) 2017 Geosfera Indonesia Journal and Department of Geography Education, University of Jember Copyright Notice This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License